Inadequate iodine intake among school children in Terengganu- findings from the National Iodine Deficiency Disorder Survey 2008. - Lim, Kuang Kuay; Chan, Ying Ying; Ahmad Ali Zainuddin,; Teh, Chien Huey; Rusidah Selamat,; Kee, Chee Cheong; Hasimah Ismail,; Lim, Kuang Hock (Universiti Kebangsaan Malaysia, 2013)
Iodine deficiency is still prevalent worldwide and it is the main cause of goiter, thyroid dysfunction and mental retardation. The aim of the study was to determine the iodine status and goiter prevalence among the school children in Terengganu.